Effects of photoperiod on the ultrastructure of Leydig cells in rat - Kus, I; Songur, A; Ozogul, C; Kavakli, A; Zararsiz, I; Sarsilmaz, M (Taylor & Francis Inc, 2004)
The aim of this study was to examine effects of photoperiod on the ultrastructure of Leydig cells in rat. For this purpose, 21 male Wistar rats were used. Animals were divided into three groups: Control rats in group I were kept under 12 hrs light: 12 hrs dark conditions (12L:12D) for 10 weeks. Animals in group II were exposed to long photoperiods (18L:6D), while rats in group III were exposed to short photoperiods (6L:18D) for 10 weeks. At the end of the experiment, all animals were killed by decapitation and blood samples were obtained. Serum testosterone levels were determined with the use of a chemiluminescent enzyme immunoassay. The testes of all rats were removed and weighed, then processed for light and electron microscopy. For morphometric comparison, diameters of seminiferous tubules in each group were measured. In rats exposed to long photoperiods, testicular weights, diameters of seminiferous tubules and serum testosterone levels were significantly increased as compared to those in control rats, whereas exposure of rats to short photoperiods resulted in a significant decrease of testicular weights, diameters of seminiferous tubules and serum testosterone levels as compared to those in control rats and rats maintained in long photoperiods. The amount of mitochondria and cytoplasmic secretory granules were increased in the cytoplasm of Leydig cells of rats exposed to long photoperiods. Furthermore, an increase in extensiveness of rough endoplasmic reticulum in the cell cytoplasm was noticed in this group, whereas a decrease in mitochondria and cytoplasmic secretory granules of the Leydig cell cytoplasm was seen in rats exposed to short photoperiods. The results of our study indicate that testicular functions increase after exposure to long photoperiods and decrease after exposure to short photoperiods.
Keywords: Leydig cell; photoperiod; rat; ultrastructure